Pengaruh Sistem Pengendalian Internal, Transaparasi dan Penerapan Aplikasi Sistem Keuangan Desa Terhadap Keberhasilan Pengelolaan Dana Desa (Studi Kasus Desa Se Kecamatan Slogohimo, Kabupaten Wonogiri) - Diva Yunia Cipta Sari; Setyaningsih SU (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This quantitative survey study was conducted in the village government environment in Slogohimo Subdistrict, Wonogiri Regency, with the main objective of testing the significance of the influence of internal control systems, transparency, and the application of village financial systems on the successful management of village funds. Using primary data collected from 60 respondents through a validated and reliability-tested questionnaire, this study applied multiple linear regression, t-test, F-test, and coefficient of determination (R2) for analysis. The results of the study indicate that internal control systems and the application of village financial systems do not have a significant influence on the success of village fund management. Conversely, transparency has been proven to have a significant influence. Collectively, the adjusted R-square value of 0.617 indicates that these three variables only contribute 38.3% to the variation in the success of village fund management.